Footstep Power Generation - Fariz Syaufiq Sadali; Mohd Nizam Katimon (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study introduces an innovative approach to energy production by harnessing human kinetic energy from footsteps to generate electricity, offering a sustainable energy source for daily use. The research focuses on the conversion of kinetic energy into electrical energy through a specially designed footstep power generation system. Emphasis is placed on the structural design, mechanism, and overall system functionality to optimize energy conversion. A prototype mechanism was developed and tested to analyze the voltage output and efficiency under varying human weights. Experimental results demonstrated a correlation between the weight of individuals and the voltage generated per step, highlighting the system's capability and efficiency in producing electrical energy. This work paves the way for practical applications of footstep power generation as a renewable and accessible energy solution.